Health System Reforms - A Review - Prema Ramachandran, Usha Rani Singh (Planning Commission Government of India, 2003)
The review of Health System Reforms in India provides a comprehensive overview of initiatives undertaken to improve healthcare access, quality, and equity across the country. Over the past five decades, significant progress has been made in infrastructure expansion, workforce development, and technological integration, resulting in improved health indicators such as increased life expectancy and reduced infant mortality rates. Despite these achievements, disparities persist across states and demographics, compounded by a dual burden of communicable and non-communicable diseases, inequitable resource distribution, and limited rural healthcare personnel. Reform efforts encompass structural, financial, and governance measures, including mainstreaming Indian Systems of Medicine & Homoeopathy, quality control, cost-recovery mechanisms, and user charges to enhance sustainability. State-specific interventions, such as telemedicine initiatives, mobile clinics, district health committees, and integrated referral systems, highlight the shift towards decentralized, participatory healthcare delivery. The reforms also emphasize addressing emerging challenges, including NCD management, environmental and occupational health, and pharmaceutical quality assurance. Overall, the reforms aim to establish an integrated, proactive, and equitable health system capable of meeting India’s evolving health needs, with a focus on preventive care, efficiency, and inclusivity.
Health Nutrition and Family Welfare Division, Planning Commission, New Delhi, December 2003
Health Nutrition and Family Welfare Division, Planning Commission, New Delhi, December 2003
Keywords: Health System Reforms; Healthcare Access; Non-Communicable Diseases; Infrastructure Development; Manpower Distribution; Governance Reforms; Financial Reforms; Primary Health Care; Telemedicine; Health Financing; Quality Assurance; Decentralization